Budaya Mamfatin Ukunrai Sebagai Paradoks Partisipasi Masyarakat Dalam Perencanaan Pembangunan Desa - Donna Isra Silaban; Imelda Nahak (Universitas Informatika dan Bisnis Indonesia, 2020)
This study aims to examine development communication in community participation in village development planning. Community participation is very important because it can guarantee the effectiveness of development programs. There are a number of obstacles to community participation in development planning. Some identified barriers are the absence of legal support (Rumensten, 2012), lack of public awareness, low quality of human resources, length of stay and hours employment type (Wijaksono, 2013), lack of socialization from the government (Sagita, 2016), poverty and limited access provided by the government (Ompusunggu, 2017), and interest of bureaucracy in planning (Mbeche, 2017). These studies, indeed, have not considered yet cultural factor leading to disinvolvement. This qualitative case study extends previous studies by revealing the culture of mamfatin ukunrai discouraging community participation in development planning in Naran Village (pseudonym), Raimanuk Subdistrict, Belu Regency. Mamfatin ukunrai is a custom considering development planning is government's duties and responsibilities. Villagers are merely the executor of development programs. This custom is a legacy of royal government system and dominates the mindset of villagers. The tradition of highly appreciating the government unwittingly creates an invisible distance between government and society. It has discouraged villagers’ participation.